2017
DOI: 10.1002/macp.201700005
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Rheological Behaviors of Polysiloxanes Presenting Densely Simple and Well‐Defined Short‐Branched Chains

Abstract: In this paper, a series of polysiloxanes, presenting different contents of densely simple and well‐defined short‐branched chains (G1–G5), are prepared by hydrosilylation of α,ω‐(dimethylvinylsiloxy)‐poly(dimethyl‐methylvinyl)siloxanes (P1–P5) with 1,1,1,3,5,5,5‐heptamethyltrisiloxane (MDHM) and characterized by 1H and 29Si nuclear magnetic resonance, Fourier transform‐infrared spectroscopy, Abbe refractometry, gel permeation chromatography, and differential scanning calorimetry. The rheological behaviors of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…[77] The idea is derived from the thermodynamic description of stress-induced crystallization and is predominant when the crystalline domains are oriented under the application of applied stress. [78][79][80] The crystalline domains are defined with lamellar structures which stack perpendicularly to the direction of the applied stress, which can thereby predict various interesting morphological features such as the number of crystal folds and size. [75] Huang et al performed in situ X-ray diffraction analysis of the crystals formed during crystallization-induced elongation in a polycaprolactone-based polymer.…”
Section: The Working Mechanism Of a Two-way Shape Memory Polymermentioning
confidence: 99%
“…[77] The idea is derived from the thermodynamic description of stress-induced crystallization and is predominant when the crystalline domains are oriented under the application of applied stress. [78][79][80] The crystalline domains are defined with lamellar structures which stack perpendicularly to the direction of the applied stress, which can thereby predict various interesting morphological features such as the number of crystal folds and size. [75] Huang et al performed in situ X-ray diffraction analysis of the crystals formed during crystallization-induced elongation in a polycaprolactone-based polymer.…”
Section: The Working Mechanism Of a Two-way Shape Memory Polymermentioning
confidence: 99%
“…[1][2][3][4] In particular, polydimethylsiloxane (PDMS) is praised for its excellent biocompatibility, high gas permeability, low glass transition temperature (T g ), low surface energy, good thermal and oxidative stability, and water repellency. [5][6][7][8] Over the past decade, supramolecular silicone materials [9,10] have attracted much attention due to their outstanding properties, such as high DOI: 10.1002/macp.202100116 stiffness, high stretchability, self-healing ability, and thermoplastic capacity. These unprecedented properties are attributed to the dynamic nature of supramolecular bonds, whose energies are low enough to allow bond exchanging under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Having multiple chain-ends and a branched architecture results in compact polymer structures, increased solubility and decreased viscosity. [1][2][3] Anionic polymerization is the optimal living chain-growth polymerization and provides control over molecular weight, dispersity (Ð), microstructure and chain-end functionality, while also enabling the synthesis of block and statistical copolymers in one-pot. [1,4,5] Such characteristics make anionic polymerization very suitable for the synthesis of branched polymer structures.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods to synthesize branched polydimethylsiloxanes have been reported in the literature. [2,9,[13][14][15][16] In 2003, Chojnowski et al reported the synthesis of star and dendritic PDMS polymers where the researchers copolymerized hexamethylcyclotrisiloxane (D 3 ) and 1,3,5-trivinyl-1,3,5-trimethylcyclotrisiloxane (V 3 ) monomers by anionic ring-opening polymerization (AROP) to achieve macromolecules with pendant vinyl groups. [9] These living copolymerizations were then terminated by using a reactive core containing four Si-Cl bonds which ultimately resulted in the formation of star-branched polymers.…”
Section: Introductionmentioning
confidence: 99%